GAPVD1 Promotes the Proliferation of Triple-negative Breast Cancer Cells by Regulating the ERK/MAPK Signaling Pathway - Wang, Lu; Zhang, Lifen; Luo, Pei; Xia, Zeyu; Shao, Shan; Ning, Qian; Gu, Shanzhi; Zhao, Xinhan; Luo, Minna (Current Cancer Drug Targets, 2025)
BackgroundTriple-Negative Breast Cancer (TNBC) accounts for 15–20% of all breast cancers and approximately 50% of breast cancer deaths. Chemotherapy remains the mainstay of systemic treatment due to the lack of effective therapy targets. Thus, more studies are urgently needed to identify new therapeutic targets in TNBC patients.MethodsGAPVD1 expression and prognosis value in breast cancer samples were explored in The Cancer Genome Atlas database (TCGA). GAPVD1 knockdown and overexpression TNBC cell lines were constructed. CCK-8 and colony formation assays were performed to detect cell viability. Flow cytometry analysis was performed to detect cell cycle variation. Western blotting was conducted to determine the levels of target genes. Finally, an enrichment analysis of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis were performed.ResultsGAPVD1 is overexpressed in breast cancer tissues and predicts poor prognosis. In vitro experiments demonstrated that GAPVD1 is correlated with cell proliferation and the cell cycle of TNBC cells. Mechanistically, alteration in GAPVD1 expression was found to be associated with cell cycle-related proteins PCNA, Cyclin A, and the activity of the ERK/MAPK signaling pathway. Consistent with these findings, enrichment analysis of GAPVD1-involving partners and signaling pathways revealed that the cellular biosynthetic process, macromolecule biosynthetic process, and cell cycle signaling are related to GAPVD1. In vivo experiment demonstrated that GAPVD1 inhibition impedes tumor growth and expression of cell cycle-related proteins.ConclusionTaken together, our results indicate that GAPVD1 may participate in TNBC cell growth by regulating the cell cycle and ERK/MAPK signaling pathway.
Keywords: ERK signaling pathway